A novel short fiber Bragg grating accelerometer based on a V-type dual mass block structure for low- and medium-frequency vibration measurements. (June 2023) - Le, Hoang-Dang; Chiang, Chia-Chin; Nguyen, Chi-Ngon; Hsu, Hsiang-Cheng
Highlights: A novel short fiber Bragg grating (FBG) accelerometer based on a dual mass block structure is presented for low- and medium-frequency vibration measurements. The theoretical research and optimization of the FBG accelerometer's natural frequency and sensitivity are performed. The stability frequency response is flat at 20–340 Hz. The linearity of the average sensitivity is approximately 66.95 pm/g. Abstract: A novel short fiber Bragg grating (FBG) accelerometer based on a dual mass block structure is presented in this paper. The sensor is established on a solid, symmetrical design comprising a V-type beam. The configuration in the FBG accelerometer causes the FBG fiber to distort twice as much when subjected to external vibration. The theoretical research and optimization of the FBG accelerometer's natural frequency and sensitivity are performed using MATLAB software, while static structural stress and modal simulation analysis are examined using ANSYS software. An experimental test is applied to evaluate the implementation of the sensors. The natural frequency of the sensor is 880 Hz, and its stability frequency response is flat in the 20–340 Hz low- to middle-frequency range. The linearity of the average sensitivity is approximately 66.95 pm/ g, and the transverse anti-interference of the FBG fiber is around 6.53%. This work proposes a suitable method to observe low- and medium-frequency vibration signals in large-scale applications.